2013
DOI: 10.4187/respcare.01519
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Hospital Resource Utilization for Prolonged Mechanical Ventilation Patients in Taiwan: A Population-Based Study

Abstract: BACKGROUND:The aging Taiwan population is expected to require vast medical resources, including prolonged mechanical ventilation (PMV). This study determined the trends in hospital resource utilization and associated factors in PMV patients in Taiwan . During the study period, stay significantly decreased, from 35.12 days to 31.61 days, whereas hospital treatment costs significantly increased, from $7,933.17 to $8,257.52 (P < .001). Considerably decreased stay and increased hospital treatment costs were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The convenience and accessibility of the Taiwan national health insurance system may increase the likelihood of treatment for MV patients [ 1 , 2 ]. Improved medical techniques may also increase the number of patients with co-morbidities who are willing to receive invasive MV [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convenience and accessibility of the Taiwan national health insurance system may increase the likelihood of treatment for MV patients [ 1 , 2 ]. Improved medical techniques may also increase the number of patients with co-morbidities who are willing to receive invasive MV [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation (MV) is among the most common therapeutic interventions in intensive care units (ICUs), and the use of MV tends to be highest in developed countries [ 1 ]. As economic conditions increase pressure to improve efficiency in medical resource utilization, hospitals have begun transferring patients who require MV but who are hemodynamically stable from ICUs into other hospital wards or other facilities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 While PMV incidence was 6.3 per 100 ventilated ICU admissions from 2002 to 2006 in the United Kingdom, 3 in Taiwan, the PMV rate fell from 94.3 to 89.38 per 100,000 persons from 2004 to 2007. 4 In the United States, a population-based study found that the incidence of tracheostomy for PMV was 24.2 per 100,000 people in 2002, and this rate had increased by nearly 200% from the previous decade. 5 Zilberberg and colleagues estimated that, based on growth trends between 1993 and 2005, the number of patients receiving PMV is expected to double between 2000 and 2020, from 252,577 to 605,898.…”
Section: Introductionmentioning
confidence: 99%
“…8 This prolonged care also accounts for 29.1% of the general ICU bed days. 4 In 2005, Medicare-eligible patients who required PMV ranked third in summative in-patient charges by diagnostic groups and first in charges per patient. 9 Despite receiving such a high level of care, 29 -49% of PMV patients died in the hospital, 10,11 only 19% could be discharged home, 10 and Ͻ50% of PMV hospital survivors survived more than 1 y.…”
Section: Introductionmentioning
confidence: 99%
“…The initial phase was defined as the first 12 months after a cancer diagnosis. Additionally, other Taiwan studies of care costs have similarly used reimbursement, rather than charges, as a proxy for medical care costs because the NHI charge for a service is not necessarily related to the actual cost of providing the service [9] [11] . In contrast, NHI costs, which are typically defined as actual payments derived from reimbursement formulas, are used to reflect the average resource utilization for a health service [11] , [12] .…”
Section: Methodsmentioning
confidence: 99%